“You Are Dead. Continue?”: Conflicts and Complements in Game Rules and Fiction - Tocci, Jason (Eludamos: Journal for Computer Game Culture, 2008)
<!–StartFragment–><!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–> <!– /* Font Definitions */ @font-face font-family:Times; panose-1:2 2 6 3 5 4 5 2 3 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:536902279 -2147483648 8 0 511 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:12.0pt; margin-left:0cm; text-align:justify; line-height:14.0pt; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:10.0pt; font-family:Arial; mso-fareast-font-family:Times; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-GB; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 70.85pt 2.0cm 70.85pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>Videogames may be the only narrative medium in which the death of the protagonist is entirely routine. This is not an inherent bias of the form, but a potentially problematic convention left over from a time when it only made sense to look at games from a rules-based perspective. Now, as game designers become more ambitious with the sorts of stories they can tell, the “die-and-retry” approach presents an impediment to fictional coherence and enjoyment of story. This article proposes that players are more interested in enjoying games for their narrative elements than some developers and theorists recognize, and considers how a number of contemporary games have been designed to reduce conflicting elements and increase complementary elements between game rules and game fiction.<!–EndFragment–>